Sodium-ion battery layer oxygen positive electrode prepared by solid-phase combustion method and preparation method of sodium-ion battery layer oxygen positive electrode
Preparation of sodium ion battery layer oxygen positive electrode through solid phase combustion method solves the problems of high water resource consumption and energy consumption in the precursor process, realizes single crystal morphology and high cycling performance, and reduces production costs and waste liquid pollution.
Patent Information
- Application Number
- CN202411619247.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-31
AI Technical Summary
During the production process of existing sodium ion battery positive electrode materials, the use of precursor processes leads to a large amount of water consumption, increase energy consumption and waste liquid pollution, and high-temperature sintering leads to uneven material morphology, affecting cycle life.
Solid-phase combustion method is used to prepare the oxygen positive electrode of sodium ion battery layer. The sodium source and nickel-ferromanganese precursor materials are mixed by ball milling, and the low-temperature fusion sintering is carried out to form a single crystal morphology, reduce the heterophase content, and optimize it through airflow wear and breakage. Granules.
The positive electrode material that achieves a single crystal morphology has better circulation and rate performance, reduces production costs and energy consumption, and reduces waste liquid pollution.
Smart Images

Figure CN119230755A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of energy materials, and in particular relates to a sodium ion battery layer oxygen positive electrode prepared by a solid phase combustion method and a preparation method thereof. Background Art
[0002] In recent decades, sodium-ion batteries (SIBs) have attracted increasing attention due to their cost and safety advantages, avoiding challenges such as limited lithium / cobalt / nickel resources and environmental pollution. Since the sodium storage performance and production cost of SIBs are mainly based on cathode performance, the development of cathode materials with large-scale production capabilities is the key to achieving the commercial application of SIBs. Therefore, the development of host materials with high energy density, long cycle life, low production cost, and high chemical / environmental stability is the key to the implementation of advanced SIBs. Among the developed cathode materials, O3-type solid transition metal oxides have attracted widespread attention due to their simple synthesis methods, high theoretical specific capacity, and sufficient sodium content.
[0003] At present, when the O3 type sodium positive electrode material uses the precursor process to sinter the single crystal morphology, the sintering temperature is continuously increased to reduce miscellaneous items. A higher temperature is required during the production process. For example, the sintering temperature of the common nickel-iron-manganese-based layered oxide sodium ion battery is 800-950°C. In order to achieve uniform fusion of metal elements at the molecular or atomic level, the common polycrystalline or single crystal precursor is a hydroxide precursor obtained by precipitation method. Its production condition is liquid phase, which will produce a large amount of alkaline waste liquid, and its environmental protection treatment cost is high. In the process of producing precursors, it is inevitable to consume a large amount of water resources, increase energy consumption and waste liquid pollution. Summary of the invention
[0004] The present application provides a sodium ion battery layer oxygen positive electrode prepared by a solid phase combustion method and a preparation method thereof, which aims to solve the problems of large-scale consumption of water resources, increased energy consumption and waste liquid pollution in the process of using precursor technology to a certain extent.
[0005] In a first aspect, the present application provides a method for preparing a sodium ion battery layer oxygen positive electrode prepared by a solid phase combustion method, comprising the following steps:
[0006] S1, weighing a certain amount of sodium source and a precursor material containing nickel, manganese and iron, and mixing them by ball milling to obtain a mixed material;
[0007] S2, placing the mixed material obtained in step (1) into an atmosphere furnace and introducing air, performing a first sintering and a second sintering in sequence, and then naturally cooling the mixture to room temperature to obtain a sintered material;
[0008] S3, crushing the sintered material obtained in step (2) to obtain the sodium ion battery layer oxygen positive electrode.
[0009] In some embodiments, the sodium source in S1 is a combination of one or more of sodium citrate dihydrate, sodium acetate, trisodium isocitrate, disodium nitrilotriacetate, and trisodium 8-hydroxy-1,3,6-pyrene trisulfonate; the precursor material of nickel-manganese-iron in S1 is a mixture of nickel source, manganese source, and iron source, and the nickel source is a combination of one or more of basic nickel carbonate, nickel acetate, nickel dimethylaminodithiocarbamate, nickelocene, and nickel acetylacetonate; the manganese source is a combination of one or more of manganese carbonate, manganese acetate, 2-methylcyclopentadiene tricarbonyl manganese, manganese acetylacetonate, and decacarbonyl manganese; the iron source is a combination of one or more of ferric citrate, ferric acetylacetonate, ferrous lactate, ferrocene, and ferrous oxalate. In the first sintering process, each substance reaches a molten state. The introduction of citrate in this scheme can form a complex with the metal cation, and this complexation helps to achieve uniform mixing of the reactants at the molecular or atomic level. As the temperature rises, the citrate reacts with oxygen in the air atmosphere, releasing a large amount of heat, which promotes the continuation of the reaction. This self-propagating combustion process helps to quickly synthesize fluffy powder.
[0010] In some embodiments, the mass ratio of the sodium source in S1 to the elements in the nickel-manganese-iron containing precursor material is Na:Ni:Mn:Fe=(0.7-1.2):(0.01-0.5):(0.01-0.5):(0.01-0.5).
[0011] In some embodiments, the ball milling mixing in S1 specifically includes: placing the materials in a planetary ball mill at a rotation speed of 200 r / min to 400 r / min for mixing for 1 h to 1.5 min.
[0012] In some embodiments, the parameters of the air introduction in S2 are: an introduction rate of 30 to 40 L / min.
[0013] In some embodiments, the process conditions of the first sintering in S2 are: temperature of 400-600° C., holding time of 3-5 hours, and heating rate of 3-10° C. / min.
[0014] In some embodiments, the process conditions of the second sintering in S2 are: temperature of 600-800° C., holding time of 12-20 h, and heating rate of 3-10° C. / min.
[0015] In some embodiments, the crushing in S3 is specifically: using a jet mill, a motor energy efficiency classification of 20 to 80 Hz, a feeding frequency of 5 to 50 Hz, a fan frequency of 10 to 100 Hz, and passing through a 325 mesh sieve.
[0016] In a second aspect, a sodium ion battery layer oxygen positive electrode prepared by the preparation method of the first aspect is provided, wherein the chemical formula of the sodium ion battery layer oxygen positive electrode is Na1+p Ni a Fe b Mn c O 2+δ , where -0.1≤p≤0.1, 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.5, -0.01≤δ≤0.01, and a+b+c=1.
[0017] In some embodiments, the particle size D50 of the sodium ion battery layer oxygen positive electrode is 3 to 5 μm, and the specific surface area is less than 0.5 m 2 / g.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention can make the positive electrode material have a single crystal morphology through rapid low-temperature combustion of the eutectic system, and low-temperature combustion can reduce the content of impurities, so the prepared sodium ion battery layer oxygen positive electrode has both a single crystal morphology and no obvious impurities. The positive electrode material provided by the present invention not only has a single crystal morphology and no internal cracks, but also can show better cycle performance and rate performance at a high voltage of 4.0V, and the sodium ion battery prepared therefrom has high capacity and excellent cycle performance.
[0020] 2. The positive electrode material particles provided by the present invention have high strength, which can inhibit the degree of particle damage of the material electrode under high compaction density. At the same time, the particles are strong and it is not easy to form internal cracks in the material during the circulation process, which inhibits the reaction between the material and the electrolyte and improves the material circulation performance.
[0021] 3. The preparation method of the positive electrode material provided by the present invention has a low sintering temperature, a wide source of raw materials, and can obtain a uniformly mixed nano-scale solid solution in the first stage of sintering, which can greatly reduce production costs, reduce energy consumption, and promote the development of my country's energy conservation and emission reduction cause. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 is an X-ray powder diffraction spectrum of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0024] Figure 2 is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0025] Figure 3 is a mapping diagram of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0026] Figure 4 is a charge and discharge curve of the sodium ion battery positive electrode material prepared in comparative example 1 of the sodium ion battery positive electrode material prepared in example 1;
[0027] Figure 5 This is a test chart of the cycle performance of Example 1 of the present invention and Comparative Example 1 at room temperature 25°C. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0030] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0031] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0032] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0033] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0034] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0035] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0037] In a first aspect, the present application provides a method for preparing a sodium ion battery layer oxygen positive electrode prepared by a solid phase combustion method, comprising the following steps:
[0038] S1, weighing a certain amount of sodium source and a precursor material containing nickel, manganese and iron, and mixing them by ball milling to obtain a mixed material;
[0039] S2, placing the mixed material obtained in step (1) into an atmosphere furnace and introducing air, performing a first sintering and a second sintering in sequence, and then naturally cooling the mixture to room temperature to obtain a sintered material;
[0040] S3, crushing the sintered material obtained in step (2) to obtain the sodium ion battery layer oxygen positive electrode.
[0041] In some embodiments, the sodium source in S1 is a combination of one or more of sodium citrate dihydrate, sodium acetate, trisodium isocitrate, disodium nitrilotriacetate, and trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate; the nickel-manganese-iron precursor material in S1 is a mixture of a nickel source, a manganese source, and an iron source, and the nickel source is a combination of one or more of basic nickel carbonate, nickel acetate, nickel dimethylaminodithiocarbamate, nickelocene, and nickel acetylacetonate; the manganese source is a combination of one or more of manganese carbonate, manganese acetate, 2-methylcyclopentadienyltricarbonyl manganese, manganese acetylacetonate, and decacarbonyl manganese; the iron source is a combination of one or more of ferric citrate, ferric acetylacetonate, ferrous lactate, ferrocene, and ferrous oxalate.
[0042] In some embodiments, the mass ratio of the sodium source in S1 to the elements in the nickel-manganese-iron containing precursor material is Na:Ni:Mn:Fe=(0.7-1.2):(0.01-0.5):(0.01-0.5):(0.01-0.5).
[0043] In some embodiments, the ball milling mixing in S1 specifically includes: placing the materials in a planetary ball mill at a rotation speed of 200 r / min to 400 r / min for mixing for 1 h to 1.5 min.
[0044] In some embodiments, the parameters of the air introduction in S2 are: an introduction rate of 30 to 40 L / min.
[0045] In some embodiments, the process conditions of the first sintering in S2 are: temperature of 400-600° C., holding time of 3-5 hours, and heating rate of 3-10° C. / min.
[0046] In some embodiments, the process conditions of the second sintering in S2 are: temperature of 600-800° C., holding time of 12-20 h, and heating rate of 3-10° C. / min.
[0047] In some embodiments, the crushing in S3 is specifically: using a jet mill, a motor energy efficiency classification of 20 to 80 Hz, a feeding frequency of 5 to 50 Hz, a fan frequency of 10 to 100 Hz, and passing through a 325 mesh sieve.
[0048] In a second aspect, a sodium ion battery layer oxygen positive electrode prepared by the preparation method of the first aspect is provided, wherein the chemical formula of the sodium ion battery layer oxygen positive electrode is Na 1+p Ni a Fe b Mn c O 2+δ , where -0.1≤p≤0.1, 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.5, -0.01≤δ≤0.01, and a+b+c=1.
[0049] In some embodiments, the particle size D50 of the sodium ion battery layer oxygen positive electrode is 3 to 5 μm, and the specific surface area is less than 0.5 m 2 / g.
[0050] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0051] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0052] Embodiment 1:
[0053] A sodium ion battery layer oxygen positive electrode prepared by solid phase combustion method and preparation method thereof: The preparation method of the positive electrode material provided in this embodiment comprises the following steps:
[0054] (1) A certain amount of sodium citrate dihydrate, basic nickel carbonate, manganese carbonate, and ferric citrate were weighed, wherein the ratio of each element was 1:0.33:0.33:0.33, and then placed in a planetary ball mill and mixed at a speed of 200 r / min for 1 hour to obtain a mixed material.
[0055] (2) The mixed material obtained in step (1) is placed into an atmosphere furnace and air is introduced at a rate of 30 L / min. The temperature is increased to 400°C at a heating rate of 3°C / min and kept at this temperature for 4 h (i.e., the first sintering). The temperature is then increased to 650°C at a heating rate of 3°C / min and kept at this temperature for 12 h (i.e., the second sintering). The mixture is then naturally cooled to room temperature to obtain a sintered material.
[0056] (3) The sintered material obtained in step (3) was crushed using a jet mill, wherein the grading frequency was 60 Hz, the feeding frequency was 15 Hz, the fan frequency was 40 Hz, and the sintered material was passed through a 325 mesh sieve to obtain the positive electrode material NaNi 0.33 Fe 0.33 Mn 0.33 O2.
[0057] Embodiment 2:
[0058] A sodium ion battery layer oxygen positive electrode prepared by solid phase combustion method and its preparation method: The preparation method of the positive electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (2), the first sintering temperature is replaced with 400°C.
[0059] Embodiment 3:
[0060] A sodium ion battery layer oxygen positive electrode prepared by solid phase combustion method and its preparation method: The preparation method of the positive electrode material provided in this embodiment is basically the same as that in Example 1, except that in step (1), the second sintering temperature is replaced with 750°C.
[0061] Embodiment 4:
[0062] A sodium ion battery layer oxygen positive electrode prepared by a solid phase combustion method and a preparation method thereof: The preparation method of the positive electrode material provided in this embodiment is basically the same as that in Example 1, except that, in step (2), the temperature is increased to 500°C at a heating rate of 8°C / min and kept warm for 3 hours, and then the temperature is increased to 760°C at a heating rate of 3°C / min and kept warm for 18 hours.
[0063] The SEM image of the positive electrode material prepared in Example 1 is shown in Figure 1 As shown, it can be seen that the synthesized positive electrode material has a single crystal ellipsoidal block morphology. The single crystal morphology with good dispersion is beneficial to enhancing the strength of the material particles, reducing the generation of cracks in the material during the battery cell cycle, and is beneficial to the battery cell cycle performance.
[0064] The XRD pattern of the positive electrode material prepared in Example 1 is shown in Figure 1 As shown, it can be seen that the positive electrode material prepared in Example 1 corresponds to a NaCrO2-type layered oxide of the R3m space group, and has a very high peak intensity and excellent crystallinity.
[0065] Figure 2 is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0066] Figure 3 is a mapping diagram of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0067] Figure 4 is a charge and discharge curve of the sodium ion battery positive electrode material prepared in comparative example 1 of the sodium ion battery positive electrode material prepared in example 1;
[0068] Figure 5 This is a test diagram of the cycle performance of Example 1 of the present invention and Comparative Example 1 at room temperature 25°C. As can be seen from the figure, the capacity of Example 1 at room temperature 25°C is increased by 15 mAh / g compared with Comparative Example 1, and the 50-cycle capacity retention rate is increased by 10%.
[0069] Comparative Example 1:
[0070] A sodium ion battery layer oxygen positive electrode prepared by solid phase combustion method and preparation method thereof: The preparation method of the positive electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (1), the corresponding compounds of each element are replaced with Ni in corresponding proportions. 0.33 Fe0.33 Mn 0.33 (OH)2.
[0071] Comparative Example 2:
[0072] A sodium ion battery layer oxygen positive electrode prepared by solid phase combustion method and preparation method thereof: The preparation method of the positive electrode material provided in this comparative example is basically the same as that in Example 2, except that in step (1), the corresponding compounds of each element are replaced with Ni in corresponding proportions. 0.33 Fe 0.33 Mn 0.33 (OH)2.
[0073] Comparative Example 3:
[0074] A sodium ion battery layer oxygen positive electrode prepared by solid phase combustion method and preparation method thereof: The preparation method of the positive electrode material provided in this comparative example is basically the same as that in Example 1, except that in step (1), the holding time of the second sintering is replaced with 24h. Increasing the holding time is conducive to the bonding between primary particles and promotes the growth of secondary particles.
[0075] Test example:
[0076] 1. The particle size D50, specific surface area and single crystal morphology of the positive electrode materials prepared in the above embodiments and comparative examples were respectively detected. The results are shown in Table 1.
[0077]
[0078]
[0079] The single crystal morphology was measured by a ZEISS Gemini SEM 360 scanning electron microscope at an accelerating voltage of 5 kV, as shown in Figure 1 shown.
[0080] 2. The positive electrode materials prepared in the above embodiments and comparative examples were respectively made into button-type batteries, and the electrochemical performance of each button-type battery was tested. The results are shown in Table 2.
[0081] Among them, the button battery assembly method is as follows: the positive electrode material, conductive agent SuperP and adhesive PVDF are prepared into positive electrode material slurry according to the mass ratio of 90:5:5 using a degassing machine, and the solid content of the slurry is adjusted to 39% by N-methylpyrrolidone (NMP). The adjusted slurry is coated on aluminum foil by an automatic coating machine, dried at 120°C in a vacuum drying oven, rolled by a roller press, and punched by a slicer. Then, the button 2032 battery is assembled in a glove box, the electrolyte is 1.2 mol / L NaClO4, the solvent is EC:PC:EMC=1:1:1 (volume ratio), the diaphragm is a glass fiber diaphragm, and a metal sodium sheet is used as the counter electrode.
[0082] The electrochemical performance test method is as follows: each button half-cell is charged and discharged on a blue electric tester in a voltage range of 2.0 to 4.0 V. 0.1C charge and discharge are performed 3 times, and the 0.1C discharge capacity and the capacity retention rate after 50 cycles of 1C are tested; it can be seen from Table 2 that the positive electrode material prepared by the preparation method provided by the present invention has higher capacity and rate performance at a high voltage of 4.0V.
[0083] Table 2 Electrical performance test results of button half-cells
[0084]
[0085]
[0086] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0087] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing a sodium ion battery layer oxygen positive electrode prepared by a solid phase combustion method, characterized in that: The following steps are involved: S1, weighing a certain amount of sodium source and nickel-manganese-iron precursor material and mixing them by ball milling to obtain a mixed material; S2, placing the mixed material obtained in step (1) into an atmosphere furnace and introducing air, performing a first sintering and a second sintering in sequence, and then naturally cooling the mixture to room temperature to obtain a sintered material; S3, crushing the sintered material obtained in step (2) to obtain the sodium ion battery layer oxygen positive electrode.
2. The preparation method according to claim 1, characterized in that: The sodium source described in S1 is a combination of one or more of sodium citrate dihydrate, sodium acetate, trisodium isocitrate, disodium nitrilotriacetate, and trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate; the precursor material of nickel-manganese-iron described in S1 is a mixture of a nickel source, a manganese source, and an iron source, and the nickel source is a combination of one or more of basic nickel carbonate, nickel acetate, nickel dimethylaminodithiocarbamate, nickelocene, and nickel acetylacetonate; the manganese source is a combination of one or more of manganese carbonate, manganese acetate, 2-methylcyclopentadienyltricarbonyl manganese, manganese acetylacetonate, and decacarbonyl manganese; the iron source is a combination of one or more of ferric citrate, ferric acetylacetonate, ferrous lactate, ferrocene, and ferrous oxalate.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the sodium source and the nickel-manganese-iron containing precursor material in S1 is Na:Ni:Mn:Fe=(0.7-1.2):(0.01-0.5):(0.01-0.5):(0.01-0.5).
4. The preparation method according to claim 1, characterized in that: The ball milling mixing in S1 specifically includes: placing the materials in a planetary ball mill and mixing them at a rotation speed of 200 r / min to 400 r / min for 1 hour to 1.5 minutes.
5. The preparation method according to claim 1, characterized in that: The parameters of the air introduction in S2 are: the introduction rate is 30 to 40 L / min.
6. The preparation method according to claim 1, characterized in that: The process conditions of the first sintering in S2 are: temperature of 400-600° C., holding time of 3-5 hours, and heating rate of 3-10° C. / min.
7. The preparation method according to claim 1, characterized in that: The process conditions of the second sintering in S2 are: temperature of 600-800° C., holding time of 12-20 h, and heating rate of 3-10° C. / min.
8. The preparation method according to claim 1, characterized in that: The crushing described in S3 is specifically as follows: using a jet mill, a motor energy efficiency classification of 20 to 80 Hz, a feeding frequency of 5 to 50 Hz, a fan frequency of 10 to 100 Hz, and passing through a 325 mesh sieve.
9. A sodium ion battery layer oxygen positive electrode obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical formula of the sodium ion battery oxygen positive electrode is Na 1+p Ni a Fe b Mn c O 2+δ , where -0.1≤p≤0.1, 0≤a≤0.5, 0≤b≤0.5, 0≤c≤0.5, -0.01≤δ≤0.01, and a+b+c=1.
10. The sodium ion battery layer oxygen positive electrode according to claim 9, characterized in that: The particle size D50 of the sodium ion battery layer oxygen positive electrode is 3 to 5 μm, and the specific surface area is less than 0.5 m 2 / g.
